Recent Agglutinated Foraminiferal Trends and Assemblages of the Sedili Besar River and Its Adjacent Offshore Area, Southeastern Peninsular Malaysia - Mahani Mohamed; Sanatul Salwa Hasan; Shamsudin Jirin (Berita Sedimentologi, 2014)
The Sedili Besar River is strongly tidally influenced and its lower areas reach into a well-developed estuary. It enters the South China Sea along the wave-dominated southeastern coast of the Malay Peninsula. A total of 103 surface sediment and 48 shallow core samples from the tidal part of the river and the adjacent offshore area of Jason Bay were studied for Recent foraminiferal assemblages. The distribution of the agglutinated foraminifera shows abundance trends from the river estuary to the shallow marine offshore. Calcareous forms increase with water depth, but agglutinated foraminifera show a reverse trend.Five biofacies zones can be differentiated based on the abundance and species diversity of the dominant agglutinated foraminifera. These coincide with the upper brackish intertidal, lower brackish intertidal, estuary mouth, beach/nearshore and inner shelf depositional settings. Identification of the assemblages within the rock record from the Malay Basin and elsewhere will help considerably in a more precise characterization of the paleoenvironments of hydrocarbon reservoir intervals.